African carnivores as taphonomic agents: Contribution of modern coprogenic sample analysis to their identification. (25th March 2018) - Campmas, E.; Stoetzel, E.; Denys, C.
Abstract: In archaeological sites, large, medium, and small vertebrate remains may have been accumulated by humans, by nonhuman predators, or both. It is now assumed that neotaphonomic referentials are essential to contribute to characterising the accumulators of fossil assemblages. However, such reference data are lacking for many areas (such as North Africa) and for several predators. In addition, most of the existing studies focus on skeleton representation, bone fragmentation, and tooth marks on noningested remains. Faeces‐containing ingested remains are still rarely considered, especially for viverrids, small or medium canids, or large felids. This paper provides new taphonomic data concerning the ingested remains of diversified prey (herbivores, lagomorphs, rodents, amphibians, fish, squamates, birds, and insects) from coprogenic samples accumulated by these predators. As expected, small or medium‐small carnivores consumed more small vertebrates than did medium‐large and large carnivores. Among the small vertebrate remains from small and medium‐small carnivore scats, limb extremities are less represented than other parts of the skeleton, whereas in meso‐macromammal remains from medium‐large and large carnivore scats, small bones (from limb extremities) are abundant. Digestion attack seems to be more developed on small vertebrate remains from small and medium‐small carnivore scats than in mesofaunal prey remains from medium‐large and large carnivore scats. Among small and medium‐small carnivores, prey from cf. fox scats (mainly microvertebrates) are more diversified, more fragmented, and more digested than in small carnivore (cf. genet) samples. Among medium‐large and large carnivores, fragmentation and digestion attack on mesofaunal remains are more intense in large carnivore (cf. leopard) scats than in medium‐large (cf. jackal/wolf) scats. Finally, in order to improve characterisation of the predator responsible for fossil faunal accumulations, we highlight here the importance of considering all the small bone fragments from sieve residues in archaeological contexts (and not only whole bones and identified bone fragments).